2010
DOI: 10.1038/ajg.2009.613
|View full text |Cite
|
Sign up to set email alerts
|

No Change in Rectal Sensitivity After Gut-Directed Hypnotherapy in Children With Functional Abdominal Pain or Irritable Bowel Syndrome

Abstract: Clinical success achieved with HT cannot be explained by improvement in rectal sensitivity. Furthermore, no association could be found between rectal barostat findings and clinical symptoms in children with FAP or IBS. Further studies are necessary to shed more light on both the role of rectal sensitivity in pediatric FAP and IBS and the mechanisms by which hypnotherapy results in improvement of clinical symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…The effect of hypnotherapy on visceral hypersensitivity is not well defined. Two studies in adult IBS patients identified a reduction in visceral sensitivity after hypnotherapy,29 30 but one trial in children failed to find this effect 31…”
Section: Discussionmentioning
confidence: 99%
“…The effect of hypnotherapy on visceral hypersensitivity is not well defined. Two studies in adult IBS patients identified a reduction in visceral sensitivity after hypnotherapy,29 30 but one trial in children failed to find this effect 31…”
Section: Discussionmentioning
confidence: 99%
“…Till now, there is evidence (mainly from adults' studies) that HT reduces autonomic reactivity [34], influences gut motility [57], and normalizes visceral sensitivity [33]. In contrast, the only intervention study which examined a sample of children and adolescents with FAP or IBS by physiological measures concluded that the symptom reduction following HT could not be explained by relief of visceral (rectal) sensitivity [50].…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for limited evidence from randomized CAM trials for chronic pain include that they are difficult to conduct, due to barriers associated with recruitment and retention (e.g., 26, 27 ). Furthermore even for CAM treatments with established empirical efficacy, there is a lack of understanding about the mechanisms of treatment effects (e.g., 28 ). Consequently there is a clear need for large-scale and rigorous trials to better understand which CAM approaches work, for whom, and in what setting, as well as any iatrogenic or interactive effects CAM treatments may have with conventional approaches.…”
Section: Discussionmentioning
confidence: 99%